Alur Pemasaran Jamur Merang di Desa Cirejag Kecamatan Jatisari Kabupaten Karawang - Erfan Erfan; Jaenudin Jaenudin (Paspalum: Jurnal Ilmiah Pertanian, 2018)
Marketing agencies and marketing agencies perform their function in the product stream from the hands of producers to consumers who require the marketing costs. The size is determined by the cost of marketing functions that have been done by the respective marketing agencies, there is a difference allowing charges on any marketing process marketing agencies. The study aims to determine the marketing flow mushroom so obtained wars waged and marketing margins obtained each marketing agencies. The method used in this study is a survey, a sample of farmers by some 30 people of 120 population people and the way census of traders by 4 people, 4 people as many wholesalers and retailers by 12 people. The study was conducted from December 2012 to January 2013, the conclusions of this research are as follows: 1. Mushroom marketing channels at Cirejag village Jatisari district of Karawang Regency where one channel is from the manufacturer directly to consumers is the best marketing channels. This is due to the channels no additional marketing costs; 2. The role of the best marketing agencies and further enhance the value of the mushroom is the treatment of large traders, where sorting is done to sort out the treatment on the quality of the I and II quality adjusted on the size and cleanliness of the fungus itself; 3. The greatest marketing margins received marketing agency that collectors of Rp. 5,000. Because the purchase price is lower than non-farmers and additional marketing costs much less than the purchase price and the cost in marketing spend and wholesalers higher marketing margins obtained by Rp. 4,000